Anticancer s-Triazine Derivatives: A Synthetic Attribute - Jain, Sonika; Jain, Pankaj K.; Sain, Shalu; Kishore, Dharma; Dwivedi, Jaya (Mini-Reviews in Organic Chemistry, 2020)
1, 3, 5-Triazine (s-Triazine) is a versatile nucleus to design and develop potent bioactive molecules for drug discovery, particularly in cancer therapy. The aim of this review is to present the most recent trends in the field of synthetic strategies made for functionalized triazine derivatives active against cell proliferation. This review article covers the synthesis of aryl methylamino, morpholino, triamino substituted triazines, antimitotic agents coupled triazines and many more. Many 1,3,5- triazine derivatives, both hetero-fused and uncondensed, have shown remarkable antitumor activities. We have highlighted various derivatives with 1, 3, 5-triazine core targeting different kinases with an aim to help researchers for developing new 1, 3, 5-triazine derived compounds for antitumor activity.
Keywords: synthesis